(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Waste disposal has become an acute problem in numerous urban centers in Nigeria. The waste disposal option in many Nigerian cities is predominantly open dumping and unsanitary landfilling. Open dump site are often cited within or close to residential neighbourhood thus becoming a public threat. Waste can contaminate surface water, ground water, soil and air through this disposal option and can pose serious public health challenges. This paper presents the physical characteristics of waste and the microbiological analysis of waste in two open dumpsites at Kutunku and Angwa-dodo areas of Gwagwalada Area Council of Federal Capital Territory Abuja. Characterization of waste was done by separating waste in the two dumpsites into distinctive components eg food waste, leaves, paper, glass, metal, etc. and then weighing separately. In the microbiological analysis, waste samples were collected from 8 open dumpsites, 4 samples were collected each from Kutunku and Angwa-dodo areas. The collected waste samples were subjected microbiological analysis using standard laboratory techniques. The result shows that the 26.07 % solid waste generated in Kutunku is composed of food waste, while that of Angwa-dodo is 33.3 %. Other components of the waste include bottle and glass, plastic bags, tin and metal, old clothes, leather and electronic waste. The bacteria identified were Escherichia coliform, Streptococci feacalis, Salmonella, Shigella, Nitrobacteria, Clostrdia, Klebsiella and Staphylococcus aureus, Aspergillus, Rhizopus, and Salmonella. The fungi identified were Aspergillus niger, mucor species and Rhizopus. The pathogenic microorganisms found in the solid waste at Kutunku are higher than those found in waste